2015
DOI: 10.2174/1567205012666150504150125
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity of Curcumin Derivatives Towards Metal-Free and Metal-Induced Amyloid-β Aggregation

Abstract: When Alzheimer's disease (AD) progresses, several pathological features arise including accumulation of misfolded protein aggregates [e.g., amyloid-β (Aβ) plaques], metal ion dyshomeostasis, and oxidative stress. These characteristics are recently suggested to be interconnected through a potential factor, metal-associated Aβ (metal-Aβ) species. The role of metal-Aβ species in AD pathogenesis remains unclear, however. To elucidate the contribution of metal-Aβ species to AD pathology, as well as to develop small… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 36 publications
(26 citation statements)
references
References 50 publications
0
25
0
Order By: Relevance
“…Results indicated that Gd-Cur could modulate Cu(II)-triggered Aβ aggregation more than metal-free or Zn(II)-induced analogues. However, Cur-Swas could not modulate Aβ aggregation with and without metal ions (Kochi et al, 2015).…”
Section: Curcumin and Alzheimer's Disease (Ad)mentioning
confidence: 80%
“…Results indicated that Gd-Cur could modulate Cu(II)-triggered Aβ aggregation more than metal-free or Zn(II)-induced analogues. However, Cur-Swas could not modulate Aβ aggregation with and without metal ions (Kochi et al, 2015).…”
Section: Curcumin and Alzheimer's Disease (Ad)mentioning
confidence: 80%
“…Curcumin can inhibit cytotoxic Cu(II)-triggered Aβ 1-42 aggregation and remodel preformed Aβ fibrils in the presence of Cu(II) [94]. Mechanistically, these effects are associated with curcumin forming a ternary complex with Cu(II) and Aβ peptide that is facilitated by simultaneous Cu(II) chelation and peptide binding [95].…”
Section: Natural Product-based Amyloid Inhibitorsmentioning
confidence: 99%
“…Elevated concentration of copper is observed in tumors and cancer tissues . In addition, copper induces Aβ aggregation; therefore, the use of a chelating agent limits the free copper concentration and leads to improvement in disease conditions . Thus, chelation of copper by curcumin has been proposed as one of the possible mechanisms, which potentially contributes to amyloid reduction, both in vitro and in animal models …”
Section: Introductionmentioning
confidence: 99%